Knockdown of LncRNA-H19 Ameliorates Kidney Fibrosis in Diabetic Mice by Suppressing miR-29a-Mediated EndMT - Shi, Sen; Song, Li; Yu, Hao; Feng, Songlin; He, Jianhua; Liu, Yong; He, Yanzheng (Frontiers in Pharmacology, 2020)
Diabetic nephropathy is the leading cause of kidney fibrosis. Recently, altered expressed or dysfunction of some long non-coding RNAs (lncRNAs) has been linked to kidney fibrosis; however, the mechanisms of lncRNAs in kidney fibrosis remain unclear. We have shown that the DPP-4 inhibitor linagliptin can inhibit endothelial-mesenchymal transition (EndMT) and ameliorate diabetic kidney fibrosis associated with DPP-4 protein levels via the induction of miR-29. Here, we found that expression of the lncRNA H19 was significantly up-regulated in TGF-β2-induced fibrosis in human dermal microvascular endothelial cells (HMVECs) in vitro, and in kidney fibrosis of streptozotocin-induced diabetic CD-1 mice. We also detected up-regulated H19 expression and down-regulated miR-29a expression in the early and advanced mouse models of diabetic kidney fibrosis. H19 knockdown significantly attenuated kidney fibrosis in vitro and in vivo, which was associated with the inhibition of the EndMT-associated gene FSP-1. We also found that the up-regulation of H19 observed in fibrotic kidneys associated with the suppression of miR-29a in diabetic mice. H19, miR-29a, and EndMT contribute to a regulatory network involved in kidney fibrosis, and are associated with regulation of the TGF-β/SMAD3 singling pathway. This study indicates that inhibition of LncRNA H19 represents a novel anti-fibrotic treatment for diabetic kidney diseases.